2016
DOI: 10.1117/1.jbo.21.9.091303
|View full text |Cite
|
Sign up to set email alerts
|

Toward more intuitive brain–computer interfacing: classification of binary covert intentions using functional near-infrared spectroscopy

Abstract: In traditional brain-computer interface (BCI) studies, binary communication systems have generally been implemented using two mental tasks arbitrarily assigned to “yes” or “no” intentions (e.g., mental arithmetic calculation for “yes”). A recent pilot study performed with one paralyzed patient showed the possibility of a more intuitive paradigm for binary BCI communications, in which the patient’s internal yes/no intentions were directly decoded from functional near-infrared spectroscopy (fNIRS). We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…In line with this, it has been demonstrated that HbO signal is more robust than HbR for motor imagery specific activation (Mihara et al, 2012). Likewise, Rezazadeh Sereshkeh et al (2018) reported that HbO signals yielded the highest accuracies in their 3-class BCI using imagined speech, and Hwang et al (2016) reported that HbO features yield more discriminative information than HbR features in 2-class communication.…”
Section: Communication Accuracymentioning
confidence: 66%
“…In line with this, it has been demonstrated that HbO signal is more robust than HbR for motor imagery specific activation (Mihara et al, 2012). Likewise, Rezazadeh Sereshkeh et al (2018) reported that HbO signals yielded the highest accuracies in their 3-class BCI using imagined speech, and Hwang et al (2016) reported that HbO features yield more discriminative information than HbR features in 2-class communication.…”
Section: Communication Accuracymentioning
confidence: 66%
“…EEG and functional near-infrared spectroscopy (fNIRS) are the two major neuroimaging modalities most frequently employed for implementing noninvasive BCIs. These methods have several advantages over invasive methods, such as being safer and offering high accessibility, a more affordable cost, scalability, and portability [5][6][7][8][9]. With the rapid development of BCI technology, increasing interest has been drawn toward hybrid BCIs, which are combinations of two or more BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the features frequently used from these windows include signal mean, signal slope, signal peak, skewness, kurtosis, variance, standard deviation, number and sum of peaks, root mean square, median, etc. (Hwang et al, 2016;Naseer et al, 2016;Liu and Hong, 2017;Hong et al, 2018b;Wibowo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%